Women's Transformational Leadership and Teacher Loyalty at SMAN 4 Sijunjung - Niza, Yesita Rosa; Jamilus, Jamilus (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The main issue addressed in this study is the limited involvement of teachers in decision-making and the low level of appreciation, which impacts organisational loyalty. This study aims to analyse the influence of female transformational leadership on teacher loyalty at SMAN 4 Sijunjung. A qualitative method with a case study design was employed. Data were obtained through in-depth interviews, observation, and document analysis, and were subsequently analysed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that female transformational leadership is implemented through moral exemplarity, participatory communication, and Islamic values such as amanah, musyawarah, and rahmah. These practices build trust and strengthen teachers’ emotional loyalty to the organisation. These findings confirm that a humanistic-religious leadership approach contributes to strengthening the school’s organisational culture. This study is limited to a single location with a limited number of informants and therefore cannot yet be widely generalised. Further research is recommended to involve more schools and employ a mixed-methods approach to obtain a more comprehensive picture